FACTORS RELATING TO THE QUALITY OF HUMAN RESOURCES IN BAHTERAMAS REGIONAL PUBLIC HOSPITAL SOUTHEAST SULAWESI PROVINCE: Quality of Human Resources - Sarewo, Putri Suchi Tulhikma; Tasnim, Tasnim; La Ode Kamalia (INDONESIAN JOURNAL OF HEALTH SCIENCES RESEARCH AND DEVELOPMENT (IJHSRD), 2020)
Background: Based on the data of the achievement of minimum service standards at Bahteramas Hospital shows that several programs have not reached the specified Minimum Service Standards. For examples, the availability of facilities and operating equipment (34.37%), customer satisfaction (74.04%) from the standard ?80%, time provision of medical records (30 minutes) from standard 10 minutes, completeness of informed concent (67.75%) of ?80%. Observing the development of human resources at the Bahteramas Hospital has not been carried out optimally, for example, such as a standardized selection and recruitment process, support for facilities, infrastructure and technology, individual commitment to organization, leadership commitment and employee work relations themselves. The purpose of this research is to analyze factors related to the quality of human resources at the Bahteramas Regional General Hospital, Southeast Sulawesi Province. Methods: Quantitative research used  a cross sectional study design.The population in this study was  around 981 people. The number of samples in this study were 277 people. The sample was determined by simple random sampling technique. The data were obtained using the chi square test. Result: The results using the chi square statistical test showed  that the value of X2  = 22,378> 3,841, the value of the training variable (X2=18,658> X2 table3,841), the value of the individual commitment variable (38,863> 3,841), the value of the reward variable (X2=51,784> X2 table =3,841), the value of the skill variable (X2=94,713> X2table= 3,841). Conclusion: There is a relationship between selection and the quality of human resources. There is a relationship between training and the quality of human resources. There is a relationship between individual commitment and the quality of human resources. There is a relationship between reward and the quality of human resources. There is a relationship between skills and the quality of human resources.